The effects of flipped learning in enhancing students’ higher order thinking skills in the ESL reading classroom / Salsabilla Hassanuzin - Hassanuzin, Salsabilla (2022)
The integration of blended learning has proven that learning can be more impactful and meaningful for the English as Second Language (ESL) classroom. Yet, with limited classroom time and passive learning environments, they have been found to hinder learning processes which can be solved through flipped learning. Flipped learning was popularized by Bergman and Sams and practiced in Khan Academy before 2010. The traditional lesson is delivered outside the classroom in the flipped classroom, while the homework or assignments are done inside the classroom. Elements like learner autonomy, blended learning, and the application of Higher Order Thinking Skills (HOTS) especially in the reading classroom are the central focus of this study. Research on the implementation of flipped learning with ESL reading to gauge HOTS is very scarce. Therefore, this study applied a quantitative approach in describing the flipped learning treatment on ESL learners in the reading classroom in relation to their thinking skills. This study also executed a pre and post-test to find the effects of flipped learning treatment on students’ HOTS. A Student Assessment Survey (SAS) was also administered to find out the students’ experience of HOTS application in a flipped learning environment during the ESL reading classroom. A total of 57 students taking English Proficiency Level 2 for Diploma were selected for this study. The respondents were chosen based on a purposive non-random sampling method from the pool of students taking the English course. The students who were divided into Experimental and Control Groups were given guidance throughout the experiment. The students were tested on the application of HOTS. The result of the experiment showed that there was a significant difference in the treatment of flipped learning in terms of a small increase in HOTS application in the ESL reading classroom. The SAS data showed that students preferred flipped learning, experienced improved understanding of English, learned to analyze texts better, and the educator's role helped in facilitating understanding. Thus, it is recommended that for future studies, flipped learning could explore more listening, writing and speaking skills on the HOTS application. In short, the effect of flipped learning on enhancing students’ HOTS level was significant.